Limited liability partnership: is Malaysia ready? - Chan, W.M.; Susela, D.S.; Ng, K.T.; Lee, S.L. (2008)
In Malaysia, the traditional types of business vehicles are sole-proprietorship, partnerships and companies. The sole-proprietor and partners are liable for the debts incurred in their respective businesses. For a company, the shareholders are liable only for the amount unpaid on their shares. They are thus, not liable for the debts of the company. In April 2008, the Companies Commission of Malaysia proposed a framework for limited liabilities partnership (“LLP”) to complement the existing forms of business vehicles. It is a hybrid between the traditional partnership and company, for it enjoys the benefits of both forms. Just as in an incorporated company, the liability of the partners of an LLP will be limited. Further, the LLP will enjoy a separate legal entity from its partners, and thus will not be affected by any changes in its constitution. The LLP will also enjoy the management style of a partnership, for it will not be subject to the strict management procedures of an incorporated body. The reasons given for the proposal are to spur the growth of SMEs against the backdrop of the international business environment and the enhancement of domestic business activities. This paper will discuss the proposed framework for Malaysia in relation to the rights of a creditor and a member of the public against the LLP and its partners.